Discovery of the Baijifeng impact structure in Tonghua, Jilin, China - Ming Chen; Yang Lu; Jiahao Ning; Wenge Yang; Jinfu Shu; Ho-kwang Mao (Matter and Radiation at Extremes, 2023)
An impact structure 1400 m in diameter, formed by a bolide impact, has been discovered on Baijifeng Mountain in Tonghua City in Northeast China’s Jilin province. The impact structure takes the form of a cirque-shaped depression on the top of the mountain and is located in a basement mainly composed of Proterozoic sandstone and Jurassic granite. A large number of rock fragments composed mainly of sandstone, with a small amount of granite, are distributed on the top of Baijifeng Mountain. Planar deformation features (PDFs) have been found in quartz in the rock and mineral clasts collected from the surface inside the depression. The forms of the PDFs indexed in the quartz include among others, {101̄3}, {101̄2}, and {101̄1}. The presence of these PDFs provides diagnostic evidence for shock metamorphism and the impact origin of the structure. The impact event took place after the Jurassic Period and probably much later.